Providing care to vulnerable populations: a qualitative study among GPs working in deprived areas in Montreal, Canada. (10th February 2015) - Loignon, Christine; Fortin, Martin; Bedos, Christophe; Barbeau, David; Boudreault-Fournier, Alexandrine; Gottin, Thomas; Goulet, Émilie; Laprise, Elisha; Haggerty, Jeannie L
Abstract: Background: Communication barriers between persons living in poverty and healthcare professionals reduce care effectiveness. Little is known about the strategies general practitioners (GPs) use to enhance the effectiveness of care for their patients living in poverty. Objective: The aim of this study was to identify strategies adopted by GPs to deliver appropriate care to patients living in poverty. Methods: We conducted in-depth semi-structured interviews with 35 GPs practising in Montreal, Canada, who regularly provide care to underprivileged patients in primary care clinics located in deprived urban areas. Analysis consisted of interview debriefing, transcript coding, thematic analysis and data interpretation. Results: GPs develop specific skills for caring for these patients that are responsive to their complex medical needs and challenging social context. Our respondents used three main strategies in working with their patients: building a personal connection to overcome social distance, aligning medical expectations with patients' social vulnerability and working collaboratively to empower patients. With these strategies, the physicians were able to enhance the patient–physician relationship and to take into account the impact of poverty on illness self-management. Conclusions: Our results may help GPs improve the health and care experience of their vulnerable patients by adopting these strategies. The strategies' impacts on patients' experience of care and health outcomes should be evaluated as a prelude to integrating them into primary care practice and the training of future physicians.